METHODOLOGICAL PRINCIPLES OF SCIENTIFIC RESEARCH IN PUBLIC SECTOR ACCOUNTING AND AUDITING - Iryna Drozd; Kateryna Razumova; Halyna Nazarova (State and Regions. Series: Economics and Business, 2026)
The article examines the methodological foundations of scientific research in the field of public sector accounting and auditing under the conditions of public financial management reform and the harmonization of the national accounting system with international standards. Contemporary approaches of Ukrainian scholars to the interpretation of the methodology of scientific research are analyzed, and the peculiarities of the formation of general scientific and specialized methodological principles within economic research are identified. It is established that existing methodological approaches do not sufficiently reflect the specific characteristics of public sector accounting and auditing, which are determined by the peculiarities of the regulatory framework, the budget process, information support, public financial control, and public sector auditing. The paper summarizes the content of the general scientific principles of research, including the principles of scientific objectivity, systematicity, historicism, comprehensiveness, and the unity of theory and practice. Furthermore, it substantiates the need to extend these principles through the development of specialized methodological principles tailored to the specific features of the public sector. The study proposes and substantiates the principles of regulatory relevance, information integration, verifiability of accounting data, and institutional coherence, revealing their role in ensuring the scientific validity, reliability, and practical relevance of research in public sector accounting and auditing. A conceptual framework integrating general scientific and specialized methodological principles is developed, providing a methodological basis for conducting scientific research in public sector accounting and auditing. The practical significance of the research lies in the possibility of applying the proposed methodological principles in scientific studies, the development of methodological support for public sector accounting, public auditing, and internal control, as well as in improving the regulatory and methodological framework governing the activities of public sector entities.